THE EFFECTIVENESS OF THE ROLE OF PARENTS IN ASSISTING SOCIAL SKILLS LEARNING ACTIVITIES IN ONLINE LEARNING AT THE AGE OF KINDERGARTEN (TK) CHILDREN - Puspa Isya Qoblia; Akbar Nicholas Saputra; Wahyunengsih (Program Studi Pendidikan Anak Usia Dini (PIAUD), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
This study aims to determine the role of parents in assisting social skills learning activities in online learning in Kindergarten (TK) age children. The reason for taking this research is because of the physical distancing policy which makes social activities limited. At the same time, making children's play needs become unfulfilled. So it demands not to interact directly with their friends socially. Usually studying happily at school, meeting and socializing with teachers and friends, now they are forced to study in unusual conditions, namely learning from home. The method used in this research is a survey method with quantitative research. The data collection instrument used a closed statement with these indicators adjusted to what the role of parents and those faced by children in the Covid-19 pandemic condition and distributed online. In this study, 44 parent respondents were collected from the results of distributing questionnaires via WhatsApp, Facebook broadcasts. Based on the results of the study, it was found that knowing the role of parents in assisting learning activities for social skills in online learning for Kindergarten-aged children cannot be separated from the roles and responsibilities of parents during the current pandemic which requires children to learn, play, and play. interact at home accompanied by parents.